Agricultural Land Pawn as a Social Institution in Wono Agung Village, Tulang Bawang Regency - Raswanto; FX Sumarja; Ati Yuniati (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research focuses on agricultural land pawning, distinguishing between non-agricultural and agricultural land pawning agreements. Regulations governing agricultural land pawning, such as Government Regulation in Lieu of Law No. 56/1960, aim to protect the interests of farmers, Social institutions can act as institutions that facilitate the process of providing loans with land collateral. The increase in agricultural land pawning has created several problems. There is a disproportion between the pawn holder and the landowner. The legal weakness in the pawn agreement is that it is often done orally without a written agreement. The agricultural pawn practice acts as a social institution, providing a source of informal credit for farmers who find it difficult to access formal financial institutions.